PENGARUH KUALITAS PRODUK DAN PERSONAL SELLING TERHADAP KEPUTUSAN PEMBELIAN MOBIL AGYA PADA PT. ASTRA INTERNATIONAL TBK-TSO MEDAN GATSU BRANCH - Jeffrey Jeffrey; Melly Wijaya (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2019)
This study aims to examine and analyze the effect of product quality and personal selling on Agya car purchase decisions at PT. Astra International Tbk-TSO Medan Gatsu Branch. The method used is multiple linear regression analysis. The population is 1131 consumers and the sample in this study is 101 consumers. The results of this study found that partially and simultaneously product quality and personal selling had a positive and significant effect on the purchase decision of Agya cars at PT. Astra International Tbk-TSO Medan Gatsu Branch. The coefficient of determination was 0.239; this means 23.9% of purchasing decisions can be explained by product quality and personal selling while the remaining 70.7% is explained by other variables not examined in this study.